2014
DOI: 10.1159/000365165
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor-Stroma Ratio Is an Independent Predictor for Survival in Nasopharyngeal Cancer

Abstract: Background: The tumor-stroma ratio (TSR) has been identified as a new and practicable prognostic histological characteristic of solid tumors. The aim of this study was to evaluate the prognostic value of the TSR in nasopharyngeal cancer (NPC). Patients and Methods: A total of 93 patients who presented with NPC from 2004 to 2007 were studied. Radiotherapy with or without chemotherapy was administered according to their Union for International Cancer Control (UICC) stages. The TSR was assessed visually on hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 10 publications
5
93
0
Order By: Relevance
“…TSR is a relatively simple to apply and cheap cell-based parameter, which is a strong quality. Multiple other studies have confirmed significant prognostic implications of the TSR not only in colon cancer, but also in other solid tumors [37–42]. Further research using a larger prospective cohort should bring this parameter closer to implementation in the TNM classification system.…”
Section: Discussionmentioning
confidence: 76%
“…TSR is a relatively simple to apply and cheap cell-based parameter, which is a strong quality. Multiple other studies have confirmed significant prognostic implications of the TSR not only in colon cancer, but also in other solid tumors [37–42]. Further research using a larger prospective cohort should bring this parameter closer to implementation in the TNM classification system.…”
Section: Discussionmentioning
confidence: 76%
“…Initially, 176 papers were generated in the primary electronic search in major databases. According to the inclusion criteria, 14 eligible studies [1023] with 15 datasets and published from 2007 to 2015 were included. The main characteristics of the included studies were listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In regard to NPC, research now also shows that stroma-rich NPCs are associated with poor prognosis and an increased risk of relapse. 22 Therefore, it could be postulated that NPCs with high ADCs are more likely to have a poor outcome compared with those with low ADCs. Currently, there are only a few NPC DWI studies that have correlated diffusion parameters with tumor characteristics at diagnosis, such as T-stage, 23,24 early intratreatment response, 25 and posttreatment response.…”
Section: Discussionmentioning
confidence: 99%